Students’ Smoking Profile at Sukatani Village, Purwakarta - Cindra Paskaria; Fransisca Fransisca; Jeanastasia Kurnia; Zaneth Gunawan; Decky Gunawan (Jurnal Respirologi Indonesia, 2018)
Background: Smoking habits had become a culture in various nations in the world. The World Health Organization (WHO) estimates that tobacco use is responsible for the deaths of about six million people worldwide each year. In Indonesia, 32,1% of students had ever used any smoked tobacco product. Purpose of this study is to analyze smoking profile and CO concentration on students. Method: This study was an observational analytic with cross sectional design. Data collection through survey and CO measurements by smokerlyzer CO breath test on 98 students at Sukatani Village, Purwakarta. Results: The proportion of students who smoking was 45,92%, the existence of smokers role model in the family influenced smoking behaviour in those students OR=5,724 (p=0,001). There was significant difference of CO concentration in each group (active smokers, passive smokers, and non-smokers) with p value